Dampak Digitalisasi Rantai Pasok terhadap Praktik Operasi Ramping pada Perusahaan Distributor Makanan Kucing - Ervina Kencana, Maharani; Santosa, Wahyuningsih (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2024)
The development of digital technology has completely changed the business paradigm, introducing efficiencies and innovations that change the way companies operate. Digitalization in the logistics industry is becoming increasingly strategically important for businesses as it has a significant impact on paradigms, business models and industry boundaries. Lean operations practices, which emphasize reducing waste and increasing productivity, are the key to achieving this goal. This research aims to investigate how the adoption of digital technology in the supply chain affects lean operations practices, as well as evaluate the positive impact of supply chain digitalization on the efficiency and effectiveness of lean operations. Sampling in this research used a non-probability sampling method with purposive sampling technique. The sample in this study used 153 respondents who met the researchers' criteria. The data analysis method used was SPSS software. The results of this research show the variables that have the most influence on the company studied.